2015
DOI: 10.5812/hepatmon.32145
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Ala133Ser Polymorphism and Methylation in Ras Association Domain Family 1A Gene With Unfavorable Prognosis of Hepatocellular Carcinoma

Abstract: Background:The functional and prognostic significance of Ras association domain family 1A gene (RASSF1A) on hepatocellular carcinoma (HCC) has not been well characterized.Objectives:This study aimed to investigate the association between Ala133Ser polymorphism or promoter methylation in RASSF1A and the prognosis of HCC in Nantong City, one of the areas with the highest incidence of cancer in China.Patients and Methods:Using peripheral blood plasma, the incidence rate of RASSF1A Ala133Ser in 235 controls and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Apart from the selection of the detection technique and thresholds, the determination of the precise genomic positions of those CpG dinucleotides analyzed is also of great importance [ 86 ]. With regards to clinical heterogeneity, only 20.5% (9/44) of our enrolled articles mentioned the presence or absence of preoperative treatment [ 38 , 40 , 41 , 45 , 47 , 50 , 53 , 55 ]. Some studies suggested that both radiotherapy and chemotherapy can alter a patient’s DNA methylation status; therefore, the type of preoperative treatment performed should be clarified [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the selection of the detection technique and thresholds, the determination of the precise genomic positions of those CpG dinucleotides analyzed is also of great importance [ 86 ]. With regards to clinical heterogeneity, only 20.5% (9/44) of our enrolled articles mentioned the presence or absence of preoperative treatment [ 38 , 40 , 41 , 45 , 47 , 50 , 53 , 55 ]. Some studies suggested that both radiotherapy and chemotherapy can alter a patient’s DNA methylation status; therefore, the type of preoperative treatment performed should be clarified [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that Ras Association Domain Family 1A (RASSF1A) is a tumor suppressor gene that is implicated in the ras signaling pathway and has been shown to play a critical role in apoptosis, cell-cycle regulation, and microtubule stability 6 7 . Numerous tumor tissues including HCC are lacking RASSF1A expression due to hypermethylation of its promoter region 8 9 10 . This hypermethylation is associated with distant metastasis and low survival rates of patients after tumorectomy, making it a molecular marker for predicting HCC prognosis 11 12 .…”
mentioning
confidence: 99%
“…Apart from the selection of the detection technique and thresholds, the determination of the precise genomic positions of those CpG dinucleotides analyzed is also of great importance [86]. With regards to clinical heterogeneity, only 20.5% (9/44) of our enrolled articles mentioned the presence or absence of preoperative treatment [38,40,41,45,47,50,53,55]. Some studies suggested that both radiotherapy and chemotherapy can alter a patient's DNA methylation status; therefore, the type of preoperative treatment performed should be clari ed [87,88].…”
Section: Discussionmentioning
confidence: 99%